Dengue virus neutralizing antibody: a review of targets, cross-reactivity, and antibody-dependent enhancement - Sarker, Animesh; Dhama, Nidhi; Gupta, Rinkoo Devi (Frontiers in Immunology, 2023)
Dengue is the most common viral infection spread by mosquitoes, due to which it is prevalent in the tropical countries. The acute dengue virus infection is benign and mostly ended with febrile illness. However, secondary infection with alternative serotypes can worsen the condition, leading to severe and potentially fatal dengue. Many neutralizing antibodies have been identified against the dengue virus, which is thought to be useful to reduce dengue severity. However, for the therapeutic application, an antibody must be free from antibody-dependent enhancement effect as it is quite common in dengue infection, which escalates disease severity. Therefore, the dengue virus-neutralizing antibodies, their cross-neutralizing potency, and serotype specificity have been critically discussed here. In this review, we have also attempted to deliver wide-ranging information on cross-reactive epitopes, and the technologies to modify the cross-neutralizing antibodies, which would provide significant insights into developing safe and effective antibody therapeutics as well as equivalent protein subunit vaccines.